PENGARUH MARKETING MIX DALAM PENGAMBILAN KEPUTUSAN MEMILIH HOTEL MELATI DI KUTA-BALI - Agung Permana Budi (Jurnal Ilmiah Hospitality Management, 2012)
Marketing Mix is a major element in seeing the success of a business, usually used to describe a sales tactic in a given market. In this study the authors looked at the marketing mix in the hospitality industry, particularly in the budget hotel in Kuta-Bali. Based on the discussion of the elements of the Marketing mix variables Product, Price, Promotion, and Place simultaneously influence the purchasing decisions of consumers visits count test F is F (53.336)> F table (2.51) then Ho is rejected. While partially each variable, namely product, price, promotion and place seen from the Standardized Beta Coefficients for Product variable (X1), Price (X2), Promotion (X3) and Place (X4) are respectively 0.199 (X1 ), 0.018 (X2), 0.014 (X3) and 0.697 (X4). This means that the variable Place has the beta coefficient 0.697, according to that result, means that the variable Place is dominant influence on the decision to choose Budget Hotel In Kuta - Bali compared with other variabel in Marketing Mix